Asuhan Keperawatan pada Pasien Post Operasi Laparatomi dengan Teknik Relaksasi Deep Breathing Terhadap Tingkat Nyeri Anak di RSU Kabupaten Tangerang - Janiah Janiah; Ria Setia Sari; Suhati Suhati (Pusat Riset dan Inovasi Nasional, 2024)
Post-laparotomy pain is very intense pain originating in the area of the stomach that has been cut and requires treatment. This pain cannot be classified into an etiological group, because there are many conditions that cause it. Based on a preliminary study conducted at the Tangerang Regency General Hospital, there were 77 patients with a diagnosis of post laparotomy appendicitis starting from November-January 2024. Meanwhile, in the Lower Kemuning ward, it was found that during the assessment there was 1 case of a child with a diagnosis of post laparotomy appendicitis on the 8th. January 2024. The results of this study used deep breathing relaxation techniques to reduce pain in patients with post laparotomy appendicitis. The conclusion of this research is that the deep breathing relaxation technique is a non-pharmacological technique for reducing pain and can be used in patients who experience post-operative pain problems. The suggestion from this research is that intervention can be carried out by medical personnel to reduce the intensity of pain in patients after laparotomy surgery.